Dynamic future-proofing : integrating disruption in everyday business - Manu, Alexander, 1954- (Emerald Publishing Limited, 2021)
The ability to achieve business goals by incorporating disruptive technologies as driving forces is critical to an organization's survival. This book prepares executives for the challenge of creating a culture of exploration and shaping strategic transformation in times of profound disruption. How can leaders bridge the gap between business competence and the creation of new wealth? Understanding that disruption moves society from one level of existence to the next, the author demonstrates that to be future proof, leaders must demonstrate their ability to adapt to changing dynamics with creativity and complex thinking to ensure that they learn and innovate at the same time. Showing readers how tactical agility in future proofing enables employees at all levels to innovate, and take intelligent risks whilst pursuing a clear strategy, Manu showcases how strategic agility in future proofing enables organizations as a whole to identify new trends and changes in the business environment, and empowers individuals to adapt dynamically to new realities. Recognising that companies which respond to disruptions in the early stages of amplification can convert potentially existential threats into transformative opportunities, this book shows us how good leadership, intelligent informed opinion, and rapid action in a time of change can help organizations not only to predict the future, but create it.